Presidential Decree-Law No. 47/2014 On Amending Certain Provisions f the Public Cleanliness Law No. 38/1967 - egypt (2025)
Presidential Decree-Law No. 36 of the year 2014 amending certain provisions of the public cleanliness law no. 38 of the year 1967 as amended by law no. 106 of the year 2012 قرار رئيس جمهورية مصر العربية بالقانون رقم 47 لسنة 2014 بتعديل بعض أحكام القانون رقم 38 لسنة 1967 فى شأن النظافة الامة المعدل بالقانون رقم 106 لسنة 2012